Pelaksanaan pentaksiran berasaskan sekolah (PBS) Sekolah Menengah Agama Bantuan Kerajan di Daerah Muar dan Ledang - Rasul, Mohd. Salihudin (2014)
School – based assessment (SBA) is a process of monitoring , evaluating and implementing plans to address perceived weaknesess and strengths pf the school . Today policymakers and educators are looking towards SBA as a catalyst for eduvation reform. Since the late 1990s and thr beginning of 2000 , SBA slowly made its way into the Malaysians classroom .Since than, they have been a few studies that looked into the implementation of SBA in Malaysia. Therefore the study was conducted to investigate the knowledge and practices of teachers conducting the SBA programme in school. Such a study is deemed timely and crucial as it could provide a relevant picture for scholars, practitioners and policy makers in relation to testing and assessment . Descriptive research design was employed to examine the level of knowledge and indicated the problems in SBA. The study indicated the problems in SBA have to be addressed . The respondence needed to work as a team and shared their problems as an alternative to overcome the burden of the work load.